Exercise for the prevention and treatment of low back, pelvic girdle and lumbopelvic pain during pregnancy: a systematic review and meta-analysis. Issue 2 (18th October 2018) - Davenport, Margie H; Marchand, Andree-Anne; Mottola, Michelle F; Poitras, Veronica J; Gray, Casey E; Jaramillo Garcia, Alejandra; Barrowman, Nick; Sobierajski, Frances; James, Marina; Meah, Victoria L; Skow, Rachel J; Riske, Laurel; et al.
Abstract : Objective: The purpose of this review was to investigate the relationship between prenatal exercise, and low back (LBP), pelvic girdle (PGP) and lumbopelvic (LBPP) pain. Design: Systematic review with random effects meta-analysis and meta-regression. Data sources: Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs were eligible (except case studies and reviews) if they were published in English, Spanish or French, and contained information on the population (pregnant women without contraindication to exercise), intervention (subjective or objective measures of frequency, intensity, duration, volume or type of exercise, alone ["exercise-only"] or in combination with other intervention components [eg, dietary; "exercise + co-intervention"]), comparator (no exercise or different frequency, intensity, duration, volume and type of exercise) and outcome (prevalence and symptom severity of LBP, PGP and LBPP). Results: The analyses included data from 32 studies (n=52 297 pregnant women). 'Very low' to 'moderate' quality evidence from 13 randomised controlled trials (RCTs) showed prenatal exercise did not reduce the odds of suffering from LBP, PGP and LBPP either in pregnancy or the postpartum period. However, 'very low' to 'moderate' quality evidence from 15 RCTs identified lower pain severity during pregnancy and the early postpartum period in women who exercised during pregnancy (standardised mean difference −1.03, 95% CI −1.58, –0.48) compared with those who did not exercise. These findings were supported by 'very low' quality evidence from other study designs. Conclusion: Compared with not exercising, prenatal exercise decreased the severity of LBP, PGP or LBPP during and following pregnancy but did not decrease the odds of any of these conditions at any time point.